Stilistika dalam Qashiidah Sa’dunā Fiddunyā Karya Habib Ahmad Bin Muhammad Al-Muhdhor / Stylistics in Qasidah of Sa’dunā Fiddunyā By Habib Ahmad bin Muhammad Al-Muhdhor - Ulyah Darajah; Aisyam Mardliyyah (Diwan : Jurnal Bahasa dan Sastra Arab, 2020)
يهدف هذا البحث ان يعرف أساليب القصيدة "سعدنا في الدنيا" التي يسمع في أوساط المجتمع الآن.  كثير من الناس ينشدون هذه القصيدة. اشتهر هذه القصيدة بعد يذهب شيخنا"(ميمون الزبير). شهر القصيدة ليس ليبذهب (ميمون الزبير)، ولكن في هذه القصيدة هناك جمال من حيث الصوتيات والصرفية والنحوية والتصوير. البحث تدخل من مباحث النوعية و دراسة الأدبية (بحث المكتبة).يستخدم هذه الطريقة ان يوضح القصيدة بنظرية الأسلوبية.  نظرية الأسلوبية يوضح أسلوب في هذه القصيدة بتحليل الأسلوب.  و الحاصل من هذا البحث نال الصوامت و الصوائت في القصيدة. اتخذ النائب الفاعل في هذه القصيدة و استعمل تكرار الصدارة وتكرار الختاميّ والتقفية والكناية.  يظهر تحليل هذه الأسلوب أنه في القصيدة "سعدنا في الدنيا" من الكلمات والبيت هناك جمال من حيث الصوتيات والصرفية والنحوية والتصوير.الكلمات االأساسية  :أ سلوبية ، قصيدة "سعدنا في الدنيا Habib Ahmad  AbstractThis article aims to find out the styles in qasidah of Sa’dunā fiddunya, which are listened to everywhere. The qasidah of Sa’dunā fiddunya is sung by many people. The qasidah became famous after Mbah Maemun’s decease. The qasidah is famous not only because of Mbah Maemun’s decease, but this is because there is beauty in terms of phonological, morphological, syntactic, and imagery in this qasidah. This research uses qualitative methods and literature studies (library research). By applying this method, the researchers describe how to see the qasidah of Sa’dunā fiddunya with the help of theoretical theory. The theory of stylistics describes how the shape of the style uses parts of stylistic analysis. The results of this research are sawamit and sawait in the qasidah of Sa’dunā fiddunya. This qasidah does not mention the file directly, but the writer prefers the file to be hidden. This article also uses anaphora, ephipore, rhyme, and metonymy styles. The analysis of this stylistics shows that in the qasidah of the Sa’duna fiiddunya in the words, couplets, and lines, there is beauty in phonological, morphological, syntactic, and imagery terms.